2015
DOI: 10.1002/ajoc.201500038
|View full text |Cite
|
Sign up to set email alerts
|

Activating Thiolate‐Based Imidoalkylidene Tungsten(VI) Metathesis Catalysts by Grafting onto Silica

Abstract: DedicatedtoProfessor Ei-ichi Negishi on the occasion of his 80 th birthday.Abstract: In view of the strong s-donor ability of thiolate ligands, as ilica-supported tungsten alkylidene complex was prepared. While the activity of the molecular complex in alkene metathesis was not significant, the activity of the silica-supported analoguei sg reatlye nhanced, thus illustrating the importance of dissymmetry at the metal center in d 0 metathesis catalysts and the specific properties of surface siloxy ligands in acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 43 publications
1
13
0
2
Order By: Relevance
“…[552, 553a, 555] In the absence of ethylene, Mo and Wc atalysts show very similar activities in the metathesis of the internal olefin cis-4-nonene. [553][554][555] Theo bserved activities are:O tBu < Me 2 Pyr < SAr" < OtBu F3 < OSi(OtBu) 3 < OtBu F6 < OtBu F9 ,w hich parallels the decrease in the s-donating ability of the Xligand. [553][554][555] Theo bserved activities are:O tBu < Me 2 Pyr < SAr" < OtBu F3 < OSi(OtBu) 3 < OtBu F6 < OtBu F9 ,w hich parallels the decrease in the s-donating ability of the Xligand.…”
Section: Well-defined Silica-supported W-imido-alkylidenesmentioning
confidence: 99%
See 1 more Smart Citation
“…[552, 553a, 555] In the absence of ethylene, Mo and Wc atalysts show very similar activities in the metathesis of the internal olefin cis-4-nonene. [553][554][555] Theo bserved activities are:O tBu < Me 2 Pyr < SAr" < OtBu F3 < OSi(OtBu) 3 < OtBu F6 < OtBu F9 ,w hich parallels the decrease in the s-donating ability of the Xligand. [553][554][555] Theo bserved activities are:O tBu < Me 2 Pyr < SAr" < OtBu F3 < OSi(OtBu) 3 < OtBu F6 < OtBu F9 ,w hich parallels the decrease in the s-donating ability of the Xligand.…”
Section: Well-defined Silica-supported W-imido-alkylidenesmentioning
confidence: 99%
“…[519][520][521][522][523][524][525][526] Supporteda lkylidynes were also shownt o be active metathesis catalystp recursors. Preliminaryr eports appeared in early2 000s, [541,542] andt he applicationo fm odern characterization techniques eventually allowedf or precise controlofthe structures of thesesurface speciesand gave rise to theg enerationo fr emarkablya ctive well-defined silica-supportedMo- [543][544][545][546][547][548][549] andW-imido-alkylidenes [550][551][552][553][554][555] andmore recently W-oxo-alkylidenes [556][557][558][559][560] (Section 7.3.2.4).I nt he 1970sa nd 1980st he groups of Yermakov [561][562][563][564] andI wasawa [565,566] were thef irst to useo rganometallicp recursors (Mo(C 3 H 5 ) 4 and W(C 4 H 7 ) 4 )t op repare well-defined supported Mo and Woxides relevant to industrial systems and discriminate the activities of different oxidation states.T hese studies suggested that neither fully oxidized Mo VI /W VI nor highly reduced Mo II /W II species were responsible for the metathesis activity and that active sites likely arose from the oxidation state + IV.Recent advances in describing the redox chemistry of well-defined supported W-oxo sites in relation to alkene metathesis are discussed in Section 7.3.2.5. [441] Supportedt ungstenh ydridesr epresent as pecial classo fi nsitug enerated olefin m...…”
Section: Surface Sites In Industrial Catalystsmentioning
confidence: 99%
“…The tungsten atom lies at 0.48 Å above the plane defined by C ene , O1 and S, thus resulting in a slightly distorted Trigonal BiPyramidal (TBP) molecular geometry, where the imido ligand and the O2-Me group from the activated DME occupy the axial positions. The tungsten center is more sterically hindered than in W(NAr)(CHCMe 3 )(SAr') 2 [26], giving a slightly longer W1-S1 bond distance (2.3930(5) Å versus 2.349(5) Å). The W-N bond length (1.7486(17) Å) is in the range of usual W-N bond, and so is the W-C ene one (1.915(2) Å).…”
Section: Introductionmentioning
confidence: 98%
“…Introducing a strong r-donor ligand like thiolate [24], in combination with the weak r-donation of surface silanolates [25], showed very good activity [26]. Here, we explore the formation of tungsten imido alkylidene systems with a bulky arenethiolate ligand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation